A retrospective study of risk factors for carbapenem-resistant Klebsiella pneumoniae acquisition among ICU patients - Yangmin Hu; Yanting Ping; Leiqing Li; Huimin Xu; Xiaofeng Yan; Haibin Dai (Journal of Infection in Developing Countries)
Introduction: Carbapenem-resistant Klebsiella pneumoniae (CRKP) is rapidly emerging as a life-threatening nosocomial infection. In this study, we aim to identify risk factors, especially antibiotic use, for CRKP infection among intensive care unit (ICU) patients. Methodology: This was a matched case-control study of a 67-bed ICU in a tertiary care teaching hospital from 1 January 2011 through 30 June 2013. The control cases were selected among the patients with carbapenem-susceptible Klebsiella pneumoniae (CSKP) and were matched with CRKP cases for year of ICU admission and site of infection. The clinical outcomes and antibiotic treatments were analyzed. Results: One hundred and thirty patients were included in the study (65 cases and 65 controls). Bivariable analysis showed that age of patients (p = 0.044), number of antibiotic groups (p = 0.001), and exposure to carbapenems (p < 0.001) were associated with CRKP infection. Using multivariate analysis adjusted for age, prior hospitalization, number of antibiotic groups, and previous exposure to carbapenems, previous carbapenem exposure (p < 0.001) was identified as an independent risk factor for CRKP infection. Conclusions: These data suggest that exposure to carbapenems is an independent risk factor for CRKP infection. Patients with this clinical factor should be targeted for interventions to reduce the subsequent risk of infection.